Antenatal care follow-up decreases the likelihood of cultural malpractice during childbirth and postpartum among women who gave birth in the last one-year in Gozamen district, Ethiopia: a community-based cross-sectional study - Yeshinat Lakew Ambaw; Birhanu Wubale Yirdaw; Mulunesh Abuhay Biwota; Abebayehu Melesew Mekuryaw; Birhan Tsegaw Taye (BMC, 2022)
Abstract Background Recent evidence has found widespread reports of women experiencing cultural malpractice during childbirth in Asia and sub-Saharan African countries. Despite an endeavor made to drop maternal and neonatal mortality, Ethiopia remains amongst the highest mortality rate. Thus, strengthening antenatal care (ANC) follow-up is the midst of cultural malpractice reduction during childbirth. This study was aimed to assess the magnitude of cultural malpractice and associated factors during childbirth and postpartum among women who gave birth within one year in Gozamen district, Ethiopia. Methods A community-based cross-sectional study was conducted from November 1st to December 30th, 2019. A two-stage sampling technique was used to get a total of 600 women who gave birth within the last one year. Data were collected by using a semi-structured and pretested questionnaire. Then, data were entered into Epi info version 7.0 and exported to SPSS version 25 for analysis. Both bivariate analysis and a multivariable logistic regression model were fitted. The level of significance was declared based on the adjusted odds ratio (AOR) with its 95% confidence interval (CI) and a p-value of ≤0.05. Result The Overall magnitude of cultural malpractices during childbirth and postpartum was found to be 31.2% (95%CI: 27.8, 34.7). Out of 600 women, 203(33.9%) were delivered at home, 67(11.2%) practiced abdominal massage, 31(16.6%) avoided colostrum, 24(12.8%) practiced pre-lacteal feeding and 138 (23%) washed their baby before 24 h after delivery. Mothers who have antenatal follow-up (AOR=0.52 95%CI 0.28, 0.94), married marital relation (AOR=0.24, 95%CI:0.07, 0.89), being farmer husband occupation (AOR=6.25 (95%CI: 1.22, 30.30), parity ≥5 (AOR=5, 95%CI: 2.44, 9.52), had significant association with cultural malpractice during childbirth and postpartum. Conclusions This study showed there is an improvement in the magnitude of cultural malpractices during childbirth and postpartum, but still it's high as compared to the country's maternal health service utilization aim. A well-enforced health education program by well-trained healthcare personnel besides sufficient number of ANC visits are needed to overcome these cultural practices. Further, intervention modalities health education communication outreach programs would be very important to reduce the prevalence of cultural malpractices in the community.